ASSURE MODEL IN IMPROVING ENGLISH VOCABULARY OF GRADE 5 ELEMENTARY SCHOOL STUDENTS THROUGH INTERACTIVE SONGS AT SD HKBP MARANTHA, MEDAN - Geltri Purba; Ayudira Aruan; Rani Syafitri; Inayah Safani; George Silaen; Meisuri Meisuri (Adisam Publisher, 2025)
This study investigates the implementation of the ASSURE Model in teaching English vocabulary to Grade 5 elementary school students using interactive songs. Vocabulary acquisition is a fundamental aspect of language learning, yet many young learners struggle with traditional rote memorization methods. The ASSURE Model provides a structured instructional framework that enhances student engagement through the integration of multimedia, interactive participation, and assessment-based learning. Interactive songs, with their repetitive lyrics and rhythmic patterns, serve as an effective tool for reinforcing vocabulary retention. This research was conducted at SD HKBP Maranatha, Medan, involving a classroom of Grade 5 students. Data was collected through classroom observations, vocabulary tests, and student feedback. The results indicate a significant improvement in students' vocabulary acquisition and retention, demonstrating the effectiveness of the ASSURE Model when combined with interactive songs. The findings suggest that structured multimedia-based instruction can enhance young learners’ English vocabulary learning experience.